2020
DOI: 10.1101/2020.07.30.20165241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal and Spatial Heterogeneity of Host Response to SARS-CoV-2 Pulmonary Infection

Abstract: The relationship of SARS-CoV-2 lung infection and severity of pulmonary disease is not fully understood. We analyzed autopsy specimens from 24 patients who succumbed to SARS-CoV-2 infection using a combination of different RNA and protein analytical platforms to characterize inter- and intra- patient heterogeneity of pulmonary virus infection. There was a spectrum of high and low virus cases that was associated with duration of disease and activation of interferon pathway genes. Using a digital spatial profili… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 32 publications
(40 reference statements)
15
50
1
Order By: Relevance
“…As per their results, there was a surge in immune responses especially interferon pathways, JAK STAT pathway, collagen synthesis and antiviral genes. The study also confirmed the heterogeneity of SARS-CoV-2 infection associated with viral load and interferon pathways in multiple organs (Desai et al, 2020 ). The second dataset GSE155241 was established from RNA sequences from lung biopsy tissues and organoid models acquired from human pluripotent stem cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As per their results, there was a surge in immune responses especially interferon pathways, JAK STAT pathway, collagen synthesis and antiviral genes. The study also confirmed the heterogeneity of SARS-CoV-2 infection associated with viral load and interferon pathways in multiple organs (Desai et al, 2020 ). The second dataset GSE155241 was established from RNA sequences from lung biopsy tissues and organoid models acquired from human pluripotent stem cells.…”
Section: Discussionsupporting
confidence: 76%
“…The gene expression datasets of COVID-19 were retrieved from Gene Expression Omnibus ( https://www.ncbi.nlm.nih.gov/geo/ ) with the accessions GSE150316 (Desai et al, 2020 ) and GSE155241 (Han et al, 2020 ). The datasets housed multiple samples and we chose only the lung tissues for our study.…”
Section: Methodsologymentioning
confidence: 99%
“…1a-c). That NRF2induced genes are repressed during SARS-CoV2 infections was supported by reanalysis of another data-set building on transcriptome analysis of lung autopsies obtained from five individual COVID-19 patients (Desai et al 15 ) (Fig. 1d).…”
Section: Resultsmentioning
confidence: 82%
“…The experiment is a reanalysis of data from Blanco-Melo et al [https://doi.org/10.1101/2020.03.24.004655]. d Reanalysis of the data from Desai et al15 GEO accession code GSE150316. Heat map of NRF2 target genes of the lung autopsies from the five COVID19 patients.…”
mentioning
confidence: 99%
“…It also revealed that VDR and pro-inflammatory genes are down-regulated, while STAT1, STAT2, and interferon response genes are upregulated in the high viral load lung samples compared to the low viral lung samples of COVID-19 (Table 4 and Figures 6A, B). Desai et al reported that the COVID-19 patients classified as high viral load induced more interferon response pathway genes for antiviral defense programs, resulting in a significantly short duration of illness than patients with low viral load (37). A recent study showed that human epithelial cells infected with SARS-CoV-2 induces a high interferon response via Jak-STAT signaling pathway, which controls the viral replications and de novo virus production (56) Another study observed that type I IFNs suppress the SARS-CoV-2 activities in cultured cells, showing the potency of type I IFNs to treat COVID-19 (57).…”
Section: Ifn-a-induced Jak-stat Signaling Pathwaymentioning
confidence: 99%